The Effect Of Brand Equity, Price, And Product Quality On The Purchase Decision Of Iphone Smartphones Among Generation Z In Bengkulu City - Sinta Bela Armeni; Siti Hanila; Yudi Irawan Abi (Utami Publisher, 2026)
This study is titled “The effect of Brand Equity, Price, and Product Quality on Purchase Decision of iPhone Smartphones among Generation Z in Bengkulu City.” The purpose of this study is to determine the effect of these three variables on the purchase decisions of iPhone users. The regression analysis results show that Brand Equity, Price, and Product Quality have a positive and significant effect on Purchase Decisions, both partially and simultaneously. The significance value of each variable is 0.000 ≤ 0.05, proving that all variables have a real effect on purchase decisions of iPhone in Bengkulu City. The partial test (t-test) results show that the three independent variables have a significant effect on purchase decisions, with a significance value of 0.000 ≤ 0.05 for each variable. More specifically, the Brand Equity variable (X₁) has a significant effect on purchase decisions with a t-count of 4.513; the Price variable (X₂) also has a significant effect with a t-count of 6.531; and the Product Quality variable (X₃) has a significant effect with a t-count of 4.185. Meanwhile, the simultaneous test (F test) results show F count of 1041.083, which is greater than F table value of 2.67. Therefore, it can be concluded that the three variables together have a significant effect on purchase decision of iPhone among Generation Z in Bengkulu City. Based on the results of this study, it is recommended that Apple and iPhone distributors strengthen their brand image, adjust their pricing strategies to remain competitive without reducing the premium impression, and continue to maintain and improve product quality. Further research is recommended to add other variables such as customer loyalty or promotion to make the results more comprehensive.